Intrahepatic cholangiocarcinoma: Limitations for resectability, current surgical concepts and future perspectives. Issue 5 (May 2020) - Machairas, Nikolaos; Lang, Hauke; Jayant, Kumar; Raptis, Dimitri A.; Sotiropoulos, Georgios C.
Abstract: Intrahepatic cholangiocarcinoma (iCCA) is the second most common hepatic malignancy and its incidence has been shown to increase significantly during the past decades. Complete surgical resection is currently acknowledged as the only curative treatment option able to provide adequate long-term outcomes. We herein review technical, functional and oncologic limitations for resectability, discuss current surgical aspects as well as highlight the fields in which future research and practice should focus on in order to ameliorate long-term outcomes in patients with iCCA.